The maturity period is the main stage of antibiotic resistance genes reduction in aerobic composting process of swine manure in sub-scale farms. (January 2021) - Guo, Wei; Huang, Caihong; Xi, Beidou; Tang, Zhurui; Tan, Wenbing; Li, Wenxuan; Zhang, Ying; Li, Wei
Highlights: Maturity stage is the main reduction stage of ARGs in composting of sub-scale farm. ARGs was mainly affected by the community succession of potential host bacteria. Prolonging maturity period would inhibit the potential host bacteria of ARGs. Abstract: This study was focused on the changes of antibiotic resistance genes (ARGs) and their potential host bacteria during the swine manure composting on sub-scale farms. Eight target ARGs increased 427% on average, with a trend of increase at early stage and decrease at later stage, and the main reduction stage appeared in maturity stage. The abundance of ARGs was mainly affected by the community succession of potential host bacteria. Composting could reduce the abundance of potential host bacteria of ARGs as well as pathogens such as Pseudomonas, and reduce the environmental risks of swine manure. N/C and S levels had a positive effect on the potential host of most ARGs. Prolonging the maturity period would inhibit the growth of potential host bacteria of ARGs during composting, therefore inhibiting the transmission of ARGs.